Does bank competition alleviate credit constraints in developing countries? - Leon, Florian (Journal of Banking & Finance, 2015)
Whether competition helps or hinders firms’ access to finance, particularly in the developing world, is in itself a much debated question in the economic literature and in policy circles. This paper considers the consequences of bank competition on credit constraints using firm level data covering 69 developing and emerging countries. In addition to the classical concentration measure, competition is assessed by computing three non-structural measures (Boone indicator, Lerner index and H-statistic). The results show that bank competition alleviates credit constraints and that bank concentration measure is not a robust predictor of a firm’s access to finance. The study highlights that bank competition not only leads to less severe loan approval decisions but also reduces borrower discouragement.